ASSOCIATION OF IRON PILLS CONSUMPTION DURING PREGNANCY WITH INCIDENCE OF MATERNAL ANEMIA IN INDONESIA (IFLS 5 ADVANCED ANALYSIS STUDY) - Iswardani, Octaldina; Hakimi, Mohammad; Kurnia, Arif Rahmat (JHE (Journal of Health Education), 2019)
Background: Indonesia Family Life Survey (IFLS) data in this study focused on the consumption of iron pills (Fe) during pregnancy and maternal anemia in Indonesia (Study analysis continued IFLS 5). The aim of this research is knowing the relationship of consumption of iron pills during pregnancy with the incidence of maternal anemia in Indonesia. Methods: Study was an observational analytic study with a cross sectional design using IFLS 5 data which taken in 2014-2015. Results: From the results of multiple logistic regression tests, the variables of education, mother?s residence and history of bleeding at delivery were significantly associated with the incidence of maternal anemia with OR (95% CI) sequentially 1.38 (1.003-1.92), 0.63 (0.46-0.88) and 1.74 (1.01-3.00). While consumption of iron-added pills during pregnancy was not associated with the incidence of maternal anemia in Indonesia (p = 0.760) and OR (95% CI) = 1.05 (0.76-1.43). Conclusion: There was no significant relationship between the consumption of poor iron pills during pregnancy with the incidence of maternal anemia in Indonesia. There was a significant relationship between maternal education, maternal residence and bleeding history at birth with the incidence of anemia in the mother.